TINJAUAN HUKUM ISLAM TERHADAP PENERJEMAHAN AL-QUR’AN PER KATA ONLINE - Arinal Firdaus; Sabilul Muhtadin; Muhsan (Al-Majaalis : Jurnal Dirasat Islamiyah, 2023)
Along with the needs of Muslims for the translation of the Qur'an, various types of translations of the Qur'an emerged. Especially in this global era, Muslims are competing to provide translations of the Qur'an in digital form and make them available on websites that can be easily accessed. This study describes the review of Islamic law in the online translation of the Qur'an per word. A translation of the Qur'an by word (TQK) into Indonesian is available on websites. The purpose of this study is to explain the suitability of the practice of translating the Qur'an online word by word in accordance with Islamic law. The approach used in this research is to use a qualitative approach, which is library research, namely utilizing library resources to obtain research data. Then they were analyzed with research methods.